2000
DOI: 10.1023/a:1007684311023
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The effect of indomethacin, a non-steroidal anti-inflammatory drug upon purified calpain has been studied. Also, its effects upon Ca2+-mediated degradation of cytoskeletal proteins (neurofilament) in spinal cord homogenate has been investigated. A dose-dependent inhibition of purified calpain activity was observed. A 50% inhibition of 14C-caseinolytic activity was obtained with less than 1.1 mM of indomethacin while the activity was completely inhibited at 3.3 mM concentration. The inhibitory effect of ketorla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previously, we demonstrated that calpain mRNA and total protein expression were decreased by 72 h treatment with indomethacin or NS-398, but not SC-560, and that this was consistent with inhibition of cell migration by these drugs (Raveendran, et al, 2008). Furthermore, other laboratories had also demonstrated that NSAIDs reduce calpain protein levels (Fushimi, et al, 2004; Banik, et al, 2000). But as calpains have pleiotrophic effects on cells and distinct subcellular pools contribute to these, global assessments of calpains can be misleading.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that calpain mRNA and total protein expression were decreased by 72 h treatment with indomethacin or NS-398, but not SC-560, and that this was consistent with inhibition of cell migration by these drugs (Raveendran, et al, 2008). Furthermore, other laboratories had also demonstrated that NSAIDs reduce calpain protein levels (Fushimi, et al, 2004; Banik, et al, 2000). But as calpains have pleiotrophic effects on cells and distinct subcellular pools contribute to these, global assessments of calpains can be misleading.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our investigations suggest that cathepsins also participate in the pathogenesis of SCI and inhibition of cathepsins can be an important strategy to enhance neuroprotection in SCI. 5,54 The cleavage of Bid to tBid and degradation of anti-apoptotic Bcl-2 proteins by the lysosomal cathepsins are supposed to be the links to the release of cytochrome c from mitochondria to cytosol for eventual activation of caspase-3. 55,56 Thus, the cross-talk between the lysosomes and mitochondria is now known to be very crucial process during apoptosis.…”
Section: Contribution Of Cathepsins To Neurodegeneration and Inhibitimentioning
confidence: 99%